Assessing Potential Areas of Ecotourism through a Case Study in Ilgaz Mountain National Park - Cetin, Mehmet; Sevik, Hakan (InTech, 2016)
The changing demands of tourism provide greater benefits to tourists and generate competitive advantages that develop diversity in tourism. Elements of ecotourism fit within this context, and such tourism includes, but is not limited to, activities such as visiting natural and cultural resources without destroying nature, which are carried out with an aim toward sustainability. Ilgaz Mountain has a wealth of natural, cultural, historical, and recreational features, and its location near the Black Sea gives the area significant tourism potential. In order to evaluate the impact, potential, and possibilities of ecotourism in this protected area, we used geographic information systems (GIS) to determine the nature of protection required based on implementation availability. In this study, we used ecology-based identification of the natural and cultural values to characterize the features. The study consists of four parts: (1) the concept of ecotourism, (2) discussion of sustainable growth of tourism, (3) sustainability of ecotourism using GIS and how this is related to sustainable ecotourism in protected areas, such as in Turkey, (4) results and evaluation. By assessing these results, we aim to determine potential areas for ecotourism in terms of sustainable development, and we expect the results to provide useful ideas for further research.
Keywords: 13. Climate action; 8. Economic growth; 11. Sustainability; 15. Life on land; 12. Responsible consumption